Statistical methods in healthcare - Faltin, Frederick W.; Kenett, Ron.; Ruggeri, Fabrizio (Chichester, West Sussex, United Kingdom : Wiley, 2012)
In recent years the number of innovative medicinal products and devices submitted and approved by regulatory bodies has declined dramatically. The medical product development process is no longer able to keep pace with increasing technologies, science and innovations and the goal is to develop new scientific and technical tools and to make product development processes more efficient and effective. Statistical Methods in Healthcarefocuses on the application of statistical methodologies to evaluate promising alternatives and to optimize the performance and demonstrate the effectiveness o.
Statistical aspects in ICH guidelines / Sampson and Kenett -- Statistical methods in clinical trials / Telba Irony -- Pharmacikinetics, pharmacodynamics, and pharmacometrics / Serge Guzy -- Virtual clinical trials for streamlining drug development / Zvia Agur -- Stage wise clinical trial experiments in phase I, II and III / S. Zacks -- Risk management in drug development / Kenett -- 21st century challenges in drug development / Yafit Stark -- Bias in modeling and monitoring health outcomes / Olivia Grigg -- Disease tracking / Biggeri -- Process indicators and outcome measures in the treatment of acute myocardial infarction patients / Guglielmi [and others] -- Meta-analysis / Eva Negri -- Control charts in healthcare / Woodall, Adams, and Benneyan -- Uses & abuses of control charts in healthcare / Jordan and Benneyan -- Six sigma in health care / Shirley Coleman -- Statistical process control in clinical medicine / Winkel and Zhang -- A model for kidney allocation : data-driven optimization / Yahav -- Statistical issues in vaccine safety evaluation / Musonda -- Economics of healthcare / Manca -- Benchmarking of healthcare costs & performance / Tarricone -- Statistical issues in healthcare facilities management / O'Neill -- Health care as a service / Anne Shade -- Statistical issues in insurance/payer processes / Stavish and Popkoski -- Quality of electronic medical records / Gregori.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Medical statistics; Medical care -- Statistical methods; HEALTH & FITNESS -- Diseases -- General; HEALTH & FITNESS -- Health Care Issues; MEDICAL -- Diseases; MEDICAL -- Health Care Delivery; MEDICAL -- Health Policy; MEDICAL -- Public Health; SOCIAL SCIENCE -- Disease & Health Issues; Medical care -- Statistical methods; Medical statistics; Statistics as Topic -- methods; Data Collection; Delivery of Health Care -- statistics & numerical data; Electronic books; Electronic books